القيم الإسلامية وحدود التخييل في رواية "جوهرة الصقيع المظلم " لعلاء الدين طعيمة - ديدة, بن سالم, عمارة لخضر (Univesity of El-Oued, 2022)
إن الدراسة التي حاولنا القيام بها لمسنا من خلال التعمق في دهاليزها أن الكاتب قد استطاع أن يوظف الآلة السردية ليوصل لنا قيم الإسلام السمحة، واتخذ من بطل الرواية وهو شخصية رئيسية في السلم السردي في هذا العمل مصدرا يخرج من عنده الدعوة لتلك القيم العظيمة، ومهد لهذا الأمر بأن جعل ذلك المصدر الذي تخرج من لدنه تلك القيم محط قبول، وذلك الأمر لم يأت مصادفة بل عمد إليه الكاتب بقصد، فاندماج الفتى المصري الذي وفد من بعيد سعيا وراء هدف معين ضمن حياة مجتمع مختلف تماما يعزز إنسانية الإنسان، ويجعل الرواية تدعو إلى القيم الانسانية قبل دعوتها إلى القيم الاسلامية، وكل هذا يجعلنا نجزم إننا امام عمل ذي قيمة، وأننا بصدد موضوع لا يخلو من المتعة كما أنه لا يفتقر إلى الفائدة، فالدعوة إلى القيم بكل أشكالها من الأمور التي ترقى بالعمل الأدبي وتصل به إلى مصاف الأعمال الخالدة، وعندما نطالع التاريخ الأدبي تصادفنا أعمال كثيرة حازت ذاك الشرف وتلقفتها الأسماع وتسابق إليها المعجبون وأحيانا نجد العمل الذي يحمل بين طياته الروح الانسانية ،لا يقف عند حدود القطر الواحد بل يتعداه الى أقطار أخرى، ولا يبقى حبيس لسان واحد بل يجري على ألسن مختلفة. The study that we tried to carry out, we noticed, by delving into its corridors, that the writer was able to employ the narrative machine to communicate to us the tolerant values of Islam, and took the protagonist of the novel, who is a major figure in the narrative ladder, in this work as a source from which he calls out for those great values, and paved the way for this. The matter is that the source from whom these values have come into being accepted, and this matter did not come by chance, but rather the writer deliberately intended it, so the integration of the Egyptian boy who came from afar in pursuit of a specific goal within the life of a completely different society enhances the humanity of man, and makes the novel calls for values Humanity before inviting it to Islamic values, and all this makes us assert that we are facing a valuable work, and that we are dealing with a topic that is not without fun nor lacking in interest. As we look at literary history, we come across many works that have won that honor and have been listened to and admirers raced to, and sometimes we find work that carries with it the human spirit, does not stop at the borders of one country, but transcends it to other countries. Ri on different tongues.
Keywords: القيم- التخييل- الآلية السردية; Values - fiction - narrative mechanism